Innovations in Technology and Science Education Clinical Audit in Healthcare: Principles, Process, and Application to Patient Waiting Times - Azamat Aziz o'g'li , Akramov; M F Abuaradeh, Rami (Journal of Science in Medicine and Life, 2026)
Clinical audit is a cornerstone of quality improvement in modern healthcare, providing a systematic framework for evaluating and enhancing patient care by comparing current practices against established standards. This review outlines the fundamental principles of clinical audit, including its definition, types, benefits, and the cyclical process of implementation. The audit cycle involves identifying a problem, defining standards, collecting data, analysing results, implementing change, and re-auditing. To illustrate practical application, this paper presents a hypothetical clinical audit focused on patient waiting times in an outpatient setting. Evidence indicates that satisfaction declines after 30 minutes, and it is recommended that at least 90% of patients be seen within 30 minutes of their scheduled appointment. By auditing this key performance indicator, healthcare providers can identify inefficiencies and implement targeted interventions, ultimately improving patient satisfaction and clinical outcomes. This paper synthesises current evidence to demonstrate how clinical audit serves as an effective, cyclical quality improvement tool in contemporary healthcare settings.